PENGARUH KOMBINASI JENIS DAN DOSIS PESTISIDA NABATI TERHADAP HAMA WALANG SANGIT (Leptocorisa oratorius Fabricius) PADA TANAMAN PADI (Oryza sativa L.) - Andi Apriany Fatmawaty; Dusep Suhendar; Samsidik . (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2013)
The research was aimed to determine effect combination type and dose pesticides nabati for pest walang sangit (Leptocorisa oratoruis Fabricius) in Rice (Oryza sativa L.). This research was conducted in the Greenhouse Center for Food and Horticultural Crop Protection Banten Province in February-April 2011 with an altitude of 5 m above sea level. The results was arranged as Randomized Completely Block Design 1 factor consisting of 9 treatment specifically: A = Control, B = Ginger 3 L ha-1 (0.018 ml t-1), C = Ginger 6 L ha-1(0.037 ml t-1), D = Ginger 9 L ha-1 (0.056 ml t-1), E = Ginger 12 L ha-1 (0.075 ml t-1), F = Galanga 3 L ha-1 (0.018 ml t-1), G = Galanga 6 L ha-1 (0.037 ml t-1), H = Galanga 9 L ha-1 (0.056 ml t-1), I = Galanga 12 L ha-1 (0.075 ml t-1) which is repeated three times. The variables measured were percentage of deaths pests Walang sangit, pest attacks Walang sangit intensity. The results research shows that combination type and dose pesticides nabati non signifikan against the percentage mortality and intensity of pest attack because dose and frequency used towards per plant is too low. The intensity of pest attack Walang sangit five tail per plant within 5 days in the amount of 2,29 %.